Pengembangan modul matematika berbasis kearifan lokal budaya kampar - M Yusriadi; Zubaidah Amir M.Z; Mery Berlian (IKIP Siliwangi, 2023)
The learning module is an independent learning medium for students to better understand a material. This study aims to produce a product in the form of a Mathematics learning module based on local wisdom of Kampar culture in increasing students' understanding of mathematical concepts. This research is a research and development (R&D) study using the Borg & Gall model. data analysis technique used is descriptive analysis. This study involved 12 certified teachers and 60 grade 4 students. The average score obtained for the material expert validator was 89%, the media expert validator was 90.3% and student assessment as a practicality test was 90.8%, if averaged from the three validators, the average value of material experts, media experts and practicality test with an average value of 90%, it means that the developed module is very feasible to be tested on students.